1981
DOI: 10.1172/jci110258
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acute Alterations in Left Ventricular Relaxation and Diastolic Chamber Stiffness Induced by Hypoxia and Ischemia

Abstract: A B S T R A C T To clarify conflicting reports concerning the effects of ischemia on left ventricular chamber stiffness, we compared the effects of hypoxia at constant coronary perfusion with those of global ischemia on left ventricular diastolic chamber stiffness using isolated, perfused rabbit hearts in which the left ventricle was contracting isovolumically. Since chamber volume was held constant, increases in left ventricular end diastolic pressure (LVEDP) reflected increases in chamber stiffness. At a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(64 citation statements)
references
References 37 publications
0
63
0
1
Order By: Relevance
“…Several factors other than coronary perfusion may have participated in the initiation and persistence of diastolic dysfunction and depression in the force generating ability of the myocardium. Changes in myocardial pH and the degree ofbonding between actin and myosin (19)(20)(21), abnormalities in calcium sequestration by the sarcoplasmic reticulum (19), and increased myocardial stiffness due to myocyte loss and collagen accumulation (6,21) may all be involved in the impairment of the mechanical properties of the ventricle (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Several factors other than coronary perfusion may have participated in the initiation and persistence of diastolic dysfunction and depression in the force generating ability of the myocardium. Changes in myocardial pH and the degree ofbonding between actin and myosin (19)(20)(21), abnormalities in calcium sequestration by the sarcoplasmic reticulum (19), and increased myocardial stiffness due to myocyte loss and collagen accumulation (6,21) may all be involved in the impairment of the mechanical properties of the ventricle (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that increased stiffness during demand ischemia is due to a rise in diastolic intracellular free calcium concentration ([Ca2+]i) in ischemic ventricular myocytes, resulting in increased diastolic force development by myofilaments, and thus incomplete relaxation (4,(12)(13)(14)(15). However, during "supply" ischemia, as occurs with complete coronary artery occlusion, which would also be expected to increase diastolic [Ca2+], diastolic distensibility is initially increased (16). This paradox has been recognized (17) but factors that could account for it have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli that increase oxygen demand have been shown to have a detrimental effect on ischemic myocardium as evidenced by a decline in ischemic and postischemic contractile performance, accelerated lactate production and depletion of myocardial high energy phosphate stores (1)(2)(3)(4)(5)(6)(7). However, all of these studies were performed under conditions in which variable degrees of flow reduction were produced concomitantly with increased oxygen demand.…”
Section: Introductionmentioning
confidence: 99%